Experimental characterization, material modeling, identification and finite element simulation of the thermo-mechanical behavior of a zinc die-casting alloy. (February 2018) - Martinez Page, Maria Angeles; Hartmann, Stefan
Abstract: Many industrially manufactured parts consist of a zinc die-cast material. Since classical constitutive models cannot predict the thermo-mechanical structural behavior of such a material – which exhibits highly non-linear rate-dependent effects, distinct aging properties as well a size-dependence of thin-walled parts –, it is necessary to carry out mechanical experiments under varying conditions as a basis for constitutive modeling. In this article, one major goal is the investigation of the rate-dependence at different temperatures of a zinc die-casting alloy. On the basis of several experiments on thin-walled, cylindrical tubes of Zamak 5, a thermo-mechanically consistent thermo-viscoplasticity model without a yield surface is proposed. Moreover, a concept of material parameter identification is provided and the implementation of the model into a finite element program is shown. Finally, the applicability of the model is proven by comparing an experiment of a complex component part with finite element simulations. Highlights: Extensive thermo-mechanical experiments of zinc die-casting material under torsion, tension and compression. Provision of temperature-dependent thermal parameters. Development of a thermo-mechanically consistent constitutive model. Development of a new stress algorithm without local iterations. Validation of the simulation using a specimen with very complex geometry.